Aquatic physiotherapy in the functional knee osteoarthritis - Garbi, Fernando Pereira; Júnior, Paulo Roberto Rocha; de Souza Pontes, Natália; de Oliveira, Andressa; de Oliveira Barduzzi, Glauber; Boas, Paulo José Fortes Villas [UNESP] (FapUNIFESP (SciELO), 2021)
Physicaltherapy in patients with osteoarthritis (OA) acts to decrease pain, increase joint functionality and to promote improvement in quality of life. Objective: To analyze the effect of a structured program of aquatic physiotherapy (AP) on functional capacity (FC) and mobility of elderly people with OA. Methods: Prospective, quantitative and analytical, randomized control study. The sample consisted of 29 patients, aged 60 years or over, diagnosed with OA, randomly allocated to the intervention group (IG), composed of 17 participants who underwent BP for two months, and to the control group (CG) of 12 participants. The primary outcome was measured by the WOMAC instruments and six-minute walk test. As a secondary endpoint, the Timed Up and Go Test measured mobility. Descriptive statistical analysis was used to present the data, with mean and standard deviation values. The comparison between groups for potential confounding factors and in relation to evolution was performed using the non-parametric chisquare test, Fisher's exact test and the Kruskal-Wallis test, and Dunn's test for multiple comparisons. The differences were considered statistically significant when p < 0.05. was a significant difference in physical and parameters related to pain (p < 0.001), stiffness (p < 0.001) physical activity (p < 0.001), distance covered in six minutes (p = 0.001), and mobility (p < 0.001) when comparing IG to CG. Conclusion: The structured AP program effectively contributed to the improvement of FC and mobility of elderly people with knee OA.
Fisioterapia aquática na capacidade funcional de idosos com osteoartrite de joelho
Keywords: Aged; Osteoarthritis; Physical Therapy modalities